PENDAPATAN DAN BIAYA POKOK PRODUKSI PADI DI DAERAH ALIRAN SUNGAI (DAS) WAY SEPUTIH PROVINSI LAMPUNG - Martsilia Amartasari; Agus Hudoyo; Achdiansyah Sulaiman (Lampung University, 2020)
The objectives of this study are to analyze the revenue and the standard cost of the rice farm in Way Seputih Watershed, the Province of Lampung. The respondents were randomly chosen. The data of the rice farm were collected by interviewing rice farmers respondents in the Rainy Season (RS) 2016/2017 and the Dry Season (DS) 2017. Data were analyzed by using the economic and financial analysis. The average productivities were 5.90 ton/ha in RS 2016/2017 and 5.93 ton/ha in DS 2017. The average net revenues over the cash cost were IDR18.63 million/ha in RS 2016/2017 and IDR18.64 million/ha in DS 2017. The average net revenues over the total cost were IDR12.05 million/ha in RS 2016/2017 and IDR12.54 million/ha in DS 2017. The average standard cost for producing rice was IDR4,970/kg and its 95% confidence interval was IDR3,821/kg – IDR6,119/kg paddy.Key words: confidence interval, revenue, rice farm, standard cost